Eksplorasi Keindahan alam dan budaya Melalui Study Tour ke Pura Tanah Lot, Bali - Tamah, Jeni Vegas; Wahid, Abdul; Penta, Rafid Ula; Dewantara, Dewantara; Kanedi, Indra (Universitas Dehasen Bengkulu, 2024)
Study tour is one of the effective ways to directly learn about the natural beauty and culture of a region. This journal documents our experiences during a study tour to Tanah Lot, Bali. We explored the natural wonders, got to know the local culture, and felt the warmth of the local community. By combining direct experiences and deep reflections, we were able to enrich our understanding of the cultural richness and natural beauty of Bali.